First-principles study of phase transition, elastic and thermodynamic properties of ZnSe at high pressure - Tao Yang (Nature Portfolio, 2020)
Abstract The structural and elastic properties of ZnSe with B3 and B1 phases under different pressure have been investigated by the first principle method based on density functional theory. The obtained structural parameters of ZnSe in both B3 and B1 structures are in good agreement with the available values. The transition pressure of ZnSe from B3 to B1 was predicted as 14.85 GPa by using the enthalpy–pressure data, which is well in line with experimental result. According to the obtained elastic constants, the elastic properties such as bulk modulus, shear modulus, Young’s modulus, ductile/brittle behavior and elastic anisotropy as a function of pressure for polycrystalline of ZnSe are discussed in details. In the frame work of quasi-harmonic Debye model, the temperature and pressure dependencies of the Debye temperature and heat capacity of ZnSe are obtained and discussed in the wide ranges.